Obtaining Beneficial Food Additives From The Seeds Of The Amaranth Plant - Samandar Abdusalomov; Dilshod Shodiev (Zien Journals, 2024)
This article explores the potential of extracting beneficial food additives from the seeds of the amaranth plant and their applications in the fields of food and medicine. Amaranth seeds are a rich source of squalene, high-quality protein, essential vitamins, and amaranth oil, which collectively contribute to their significant health benefits. The discussion emphasizes the role of these additives in improving nutritional value, reducing cholesterol levels, and enhancing therapeutic applications. The study highlights the importance of amaranth seeds as a natural and sustainable resource for producing food additives that support both health and wellness.
Keywords: amaranth; medicine; squalene